Identification of a novel invariant splice site mutation of Bruton's tyrosine kinase (BTK) gene in a Malaysian family with X-linked agammaglobulinemia / Chear Chai Teng - Chear, Chai Teng (2014)
X-linked agammaglobulinemia (XLA) is a rare genetic disorder caused by mutations in the Bruton’s tyrosine kinase (BTK) gene. These mutations cause defects in early B cell development. A patient with no circulating B cells and low serum immunoglobulin isotypes was studied as were his mother and sister. Flow cytometry showed the patient lacked BTK protein expression in his monocytes while the mother and sister had 62% and 40% of the monocytes showing BTK protein expressions, respectively. Results from genetic studies revealed that the patient had a novel base substitution in the first nucleotide of intron 9 in the BTK gene, and the mutation was IVS9+1G>C. This mutation resulted in exon 9 skipping, and a loss of 21 amino acids. This defect rendered the patient susceptible to recurrent pyogenic infections, otitis media, bronchopneumonia, asthma, and failure to thrive. Genetic study revealed that both mother and sister have heterozygous alleles at the similar mutational point as in the patient, confirming that both were carriers. This study supports the necessity of combining flow cytometry and genetic study in the diagnosis of XLA and the information obtained would be useful for subsequent genetic counseling, carrier detection and prenatal diagnosis. Key words: Bruton’s tyrosine kinase, BTK gene, splice site mutation, X-linked agammaglobulinemia, exon skipping, BTK protein